µCual doctora en cielo graduada... ». La poesia femenina per als certàmens literaris amb motiu de la beatificació i canonització de Teresa de Jesús (València, 1614 i 1621; Barcelona, 1614). - GÓMEZ, VERÒNICA ZARAGOZA (Scripta)
The aim of this study is to examine the poetic compositions made by women in the three contests held in Valencia and Barcelona on the occasion of the beatification (1614) and subsequent canonization (1622) of Teresa of Jesus; two special moments for the consoli-dation of the fame of the Carmelite nun which allowed the public display and then its printing of feminine poetry. We also analyze the Catalan female participation in the con-test held in Zaragoza in 1614 for the beatification. The study is focused from a female perspective, through the review of eighteen poems signed by women which arrived to us through extensive printed relations. Throughout the commentary of the poems, we analyze the general perception that these women have about Teresa of Jesus and we focus on some of the topical images on the life and work of the founder. We affect the bio-graphical documentation of the authors, sixteen poets 'circumstances' known only by na-me and surname (s) printed in the section. We also provide some brief touches on women's perception of the Carmelite nun from Avila figure in the Catalan language area.